VITAMIN D DEFICIENCY AND GLUCOSE METABOLISM IN NON-DIABETIC ESSENTIAL HYPERTENSIVE PATIENTS. (June 2018) - Catena, C.; Colussi, G.; Novello, M.; Bertin, N.; Brosolo, G.; Palomba, A.; Duratti, A.; Sechi, L.A.
Abstract : Objective: To evaluate the association between 25-hydroxyvitamin D (25OHD) deficiency and glucose metabolism in non-diabetic essential hypertensive (EH) subjects. Design and method: In 180 EH patients (age 50 ± 12 years, 100 males), free of diabetes and cardiovascular events we evaluated clinical variables, fasting and post-oral glucose load (OGTT) levels of glucose and insulin, C-peptide, plasma lipids, serum calcium, PTH, and 25OHD levels, renal function and presence of the metabolic syndrome (MS). Results: Patients with MS had lower 25OHD levels than patients without MS (P = 0.015). The 25OHD levels were significantly and directly related to fasting glucose (r = 0.172, P = 0.021) and HDL-cholesterol (r = 0.160, P = 0.033) and inversely related to age (r = -0.247, P = 0.001), systolic blood pressure (SBP) (r = -0.147, P = 0.020), area under the curve of plasma glucose (G-AUC) (r = -0.261, P < 0.001) and insulin (I-AUC) (r = -0.153, P = 0.047), glucose at 120 min of OGTT (r = -0.241, P = 0.001), triglycerides (r = -0.182, P = 0.014), and PTH levels (r = -0.307, P < 0.001). Subjects with normal 25OHD levels (> = 30 nmol/l) had lower SBP, fasting glucose, G-AUC, I-AUC, and PTH levels than patients with 25OHD deficiency (<30 nmol/l). G-AUC was significantly and directly related to age (r = 0.252, P = 0.001), body mass index (BMI) (r = 0.252, P = 0.001), waist-circumference (r = 0.383, P < 0.001), SBP (r = 0.236, P = 0.001), alcohol intake (r = 0.222, P = 0.004), HOMA-index (r = 0.001, P < 0.001), C-peptide (r = 0.254, P = 0.001), I-AUC (r = 0.266, P < 0.001), levels of calcium (r = 0.180, P = 0.017), PTH (r = 0.182, P = 0.016), triglycerides (r = 0.207, P = 0.005), and inversely related to 25OHD (r = -0.261, P < 0.001) and HDL (r = -0.197, P = 0.008). Furthermore, G-AUC was higher in men than in women (P = 0.013). After correction for age, gender, presence of MS, serum calcium and PTH levels, I-AUC and alcohol intake, G-AUC was independently associated with age (B = 0.197, P = 0.007), male gender (B = 0.162, P = 0.026), presence of MS (B = 0.337, p < 0.001), calcium (B = 0.225, P = 0.001) and 25OHD (B = -0.158, P = 0.037) levels. Conclusions: In non-diabetic EH patients low 25OHD levels are related to G-AUC independently of insulin levels. This association could be mediated by the effect of calcium homeostasis on insulin-resistance, given that the modulation of extracellular calcium and calcium flux across cell membranes by 25OHD may affect insulin sensitivity.